2005
DOI: 10.1097/01.ta.0000196008.48461.47
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Events in Pediatric Trauma Patients: Is Prophylaxis Necessary?

Abstract: The risk of clinically significant thromboembolic event in trauma patients under age 13 is negligible. Therefore, VTE prophylaxis is unnecessary in pediatric patients with traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 12 publications
(27 reference statements)
2
35
0
2
Order By: Relevance
“…Increasing age has been documented as the most consistent risk factor for thromboembolic events [1,[4][5][6][7]. We excluded neonates and infants in our analysis to focus on DVT of the lower extremities secondary to other causes besides indwelling venous catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age has been documented as the most consistent risk factor for thromboembolic events [1,[4][5][6][7]. We excluded neonates and infants in our analysis to focus on DVT of the lower extremities secondary to other causes besides indwelling venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is lower in children; adults have at least a 7-fold increase relative risk for DVT compared to children [3]. In addition, most children with DVT have underlying disorders and predisposing factors, such as indwelling venous catheters, surgery, trauma, thrombotic disorders, or malignancy [4][5][6][7][8][9]. Our current knowledge about DVT in children is confined to a few reviews of single institution experience or multicenter registries.…”
mentioning
confidence: 95%
“…Since the mid 1990s, several registries and retrospective reviews have reported the rates of venous thromboembolism (VTE) in pediatric trauma patients from 0.7 to 4.2 per 1000 admissions [1][2][3][4][5][6][7]. Venous thromboembolism complications have been shown to independently increase inpatient costs and length of stay in young trauma patients [8].…”
mentioning
confidence: 99%
“…Es steht außer Diskussion, dass Kinder vor VTE relativ geschützt sind [7,12,20]. Auch beim Vorliegen einer familiären Thrombophilie, werden VTE typischerweise erst im Erwachsenenalter beobachtet [21,22].…”
Section: Entwicklungshämostaseologieunclassified
“…VTE Rönnen zu einer lebensbedrohlichen Pulmonalembolie und einem postthrombotischen Syndrom (PTS) führen [4,5]. VTE sind im Vergleich zu erwachsenen Patienten selten, werden aber in den letzten Jahren immer häufiger diagnostiziert [6,7]. Ursache dafür können verbesserte Überlebenschancen für Kinder mit schweren zugrunde liegenden Erkrankungen und verbesserte und leichter verfügbare Diagnoseverfahren sein.…”
Section: Introductionunclassified